Speed and Power Control of a Slip Energy Recovery Drive Using Voltage-source PWM Converter with Current Controlled Technique - Satean Tunyasrirut; Vijit Kinnares (My University, 2013)
This paper introduces the speed and power control a slip energy recovery drive using voltage-source PWM converter with current-controlled technique. The slip energy occurred in the rotor circuit is transferred back to ac mains supply through a reactor and a step up transformer. The objective of the current-controlled technique is to increase power factor of the system and to reduce low order harmonics of the input line current. The drive system is designed and implemented using a voltage source inverter in conjunction with a boost chopper for DC link voltage, instead of a conventional drive using a 6 pulse converter or a Scherbius system. The slip power is recovered by the help of a voltage source inverter (VSI) based on a current-controlled technique. In order to keep the speed of the wound rotor induction motor constant over a certain range of operating conditions, the servo state feedback controller designed by a linear quadratic regulator (LQR) is also introduced and the PI controller designed by pole placement method is also introduced in control the slip power this paper. The overall control system is implemented on DSP, oller board. A 1 kW wound motor is employed for testing. It is found that the motor speed can be controlled to be constant in the operating range of 600-1200 rpm at no load and full load. It is also found that the harmonics of the input ac line current is reduced while the ac line input power factor is increased.
Keywords: Chopper; Slip ring; Sensorless Control of Electric Motors